Pengemasan Talk Show Dalam Perspektif Manajemen Penyiaran Televisi (Studi Kasus pada Program “Polemik On TV” di iNews TV, Jakarta Untuk Meningkatkan Rating dan Share) - Shinta Kristanty (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2017)
Packaging “Polemik On TV” program certainly involves organized and systematic broadcasting management, this is related to rating and share which is the main goal of made a television program. Likewise on the talk show program “Polemik On Tv” that aired iNews TV, to improve the share of broadcasting management is required that also rests on organizational control, so that the planning stage until the evaluation phase is organized and directed. The theory used in this research is the theory of organizational control. This research method is case study, with data collecting technique that is interview, observation and study of lust. The result of this research is packing of talk show of “Polemik On TV” in improving its rating and share based on stages of broadcasting management such as Planning, Program Production, Program Execution, and Program Evaluation. All stages of broadcasting management are also based on the control of the organization that is Simple Control (Simple Control).